2015
DOI: 10.1634/theoncologist.2015-0151
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between PD-L1 Expression and the Clinical Outcomes to Vascular Endothelial Growth Factor-Targeted Therapy in Patients With Metastatic Clear Cell Renal Cell Carcinoma

Abstract: Purpose. To evaluate the maximum tolerated regimen (MTR), dose‐limiting toxicities, and pharmacokinetics of pazopanib, an oral small‐molecule tyrosine kinase inhibitor of vascular endothelial growth factor receptor, platelet‐derived growth factor receptor, and c‐Kit, in combination with paclitaxel. Patients and Methods. Pazopanib was given daily with weekly paclitaxel on days 1, 8, and 15 every 28 days. Dose levels of pazopanib (mg/day)/paclitaxel (mg/m2) were 400/15, 800/15, 800/50, and 800/80. An expanded co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 32 publications
1
28
0
2
Order By: Relevance
“…Table 1. A total of 1,644 patients were included in the 8 studies [19][20][21][22][23][24][25][26] for the metaanalysis. The 8 included studies were published between 2006 and 2016.…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%
“…Table 1. A total of 1,644 patients were included in the 8 studies [19][20][21][22][23][24][25][26] for the metaanalysis. The 8 included studies were published between 2006 and 2016.…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%
“…Tregs in the peripheral blood are increased in patients with recurrent GBs after development of resistance to VEGFR inhibitors [89]. An increased level of PD-1 expression on CD4 and CD8 T cells was reported in patients with GBs or metastatic renal cell carcinoma that is refractory to VEGFR-targeted therapy [89,109]. Previous studies have demonstrated changes in the TME using tumor specimens resected under and after Bev therapy.…”
Section: Alteration In the Tme Following Chemotherapy With Or Withoutmentioning
confidence: 99%
“…Furthermore, a relationship was not observed between PD-L2 expression and any clinicopathological parameter or patient prognosis. 54 A previous study reported that the PD-L2 expression status did not affect the outcomes of RCC patients treated with VEGF-TKI. 55 Collectively, these findings demonstrate that the expression of PD-1 and PD-L1 by infiltrating immune cells, but not tumor cells, may be involved in the development of resistance to VEGF-TKI, and suggest that sequential or combination therapy with ICI and VEGF-TKI has potential for VEGF-TKI-resistant patients.…”
Section: Relationship Between the Tumor Immune Microenvironment And Rmentioning
confidence: 95%
“…An immunohistochemical analysis of the localization of PD-1 and PD-L1 in cancer cells and immune cells in the tumor microenvironment of ccRCC tissues revealed that the number of PD-1 and PD-L1-positive tumor-infiltrating immune cells positively correlated with the World Health Organization/International Society of Urological Pathology grade and a poor prognosis in ccRCC patients. 53,54 In addition, ccRCC patients with a high number of PD-1-and PD-L1-positive tumorinfiltrating cells were more likely to exhibit resistance to VEGF-TKI. Moreover, the number of PD-1-and PD-L1-positive tumorinfiltrating immune cells was significantly higher in VEGF-TKItreated ccRCC tissue than in untreated tumors (Fig.…”
Section: Relationship Between the Tumor Immune Microenvironment And Rmentioning
confidence: 99%